Spondyloenchondrodysplasia. Issue 2 (February 1989) - Menger, H; Kruse, K; Spranger, J
Abstract : Spondyloenchondrodysplasia is a rare autosomal recessive skeletal dysplasia with vertebral dysplasia and enchondroma-like lesions in the pelvis and long bones. The vertebral bodies show dorsally accentuated platyspondyly with disturbance of ossification. Clinical abnormalities such as short stature, rhizomelic micromelia, increased lumbar lordosis, barrel chest, facial anomalies, and clumsy movements may be present. We report on four patients, three of them from one family, who showed a wide range of clinical and radiological changes to document considerable variability of expression of the mutated gene.